2021
DOI: 10.1021/acsomega.1c00809
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Intelligence-Based Model for Performance Prediction of Acid Fracturing in Naturally Fractured Reservoirs

Abstract: Acid fracturing is one of the most effective techniques for improving the productivity of naturally fractured carbonate reservoirs. Natural fractures (NFs) significantly affect the design and performance of acid fracturing treatments. However, few models have considered the impact of NFs on acid fracturing treatments. This study presents a simple and computationally efficient model for evaluating acid fracturing efficiency in naturally fractured reservoirs using artificial intelligence-based techniques. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…A number of studies confirmed the effectiveness of ML models in application to oil recovery factor estimation [14][15][16]. Several other studies have reported the successful application of ML models to estimate the effects of hydraulic fracturing [17][18][19][20]. Kornkosky et al applied multivariate linear regression to estimate the waterflooding effect [11].…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies confirmed the effectiveness of ML models in application to oil recovery factor estimation [14][15][16]. Several other studies have reported the successful application of ML models to estimate the effects of hydraulic fracturing [17][18][19][20]. Kornkosky et al applied multivariate linear regression to estimate the waterflooding effect [11].…”
Section: Introductionmentioning
confidence: 96%
“…Stimulation treatments are applied to increase the productivity of tight hydrocarbon-bearing formations. Several techniques are used, such as acidizing, hydraulic fracturing, or combined approach. Acids can be injected at high pressure to induce rough fracture surfaces during hydraulic fractures; such treatment is defined as acid fracturing . The ultimate goal of acid fracturing treatments is creating rough fracture surfaces by injecting acids at high pressure. , Increasing the roughness of fracture surfaces can increase fracture conductivity which is defined as the fracture width multiplied by its permeability. , Various factors can affect the performance of acid fracturing operations, including reservoir properties (e.g., reservoir permeability and natural fractures) and fracture properties (i.e., fracture size and conductivity). , Also, the treatment conditions such as acid concentration, injection rate, pressure, and temperature can affect the treatment performance. …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Various factors can affect the performance of acid fracturing operations, including reservoir properties (e.g., reservoir permeability and natural fractures) and fracture properties (i.e., fracture size and conductivity). 14,15 Also, the treatment conditions such as acid concentration, injection rate, pressure, and temperature can affect the treatment performance. 16−18 Several studies were conducted to optimize the efficiency of acid fracturing treatments, and experimental and simulation approaches were used.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Ameri et al (2020) employed FRACPRO software to optimize acid fracturing design for a tight carbonate reservoir to investigate the impact of acid injection stages and acid fluids types on the fracture geometry parameters and the fracture conductivity [25]. Hassan et al (2021) presented a simple and computationally efficient model for evaluating acid fracturing efficiency in naturally fractured reservoirs using artificial intelligence-based techniques [26].…”
Section: Introductionmentioning
confidence: 99%